2004
DOI: 10.1039/b410180d
|View full text |Cite
|
Sign up to set email alerts
|

A concise total synthesis of (+)-okaramine C

Abstract: The first total synthesis of (+)-okaramine C is described. Our previously described selenocyclisation-oxidative deselenation sequence was used to establish a 3a-hydroxy-pyrrolo[2,3-b]indole core, which was modified by selective epimerisation to the common pyrrolo[2,3-b]indole of the okaramines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Signals for the four protons at positions 4, 5, 6 and 7 of the indole ring were clearly observed (Table S1), and revealed that the prenyl moiety is connected to N-1 or C-2 of the indole ring. The signals of the methyl groups in the reverse prenyl moieties attached to C-2 of the indole rings of some diketopiperazine derivatives, for example, in echnulin-and isoechinulin-type alkaloids, [2][3][4] in deoxybrevianamide E [5] or okaramines, [6,7] were usually found in the range of 1.40 to 1.55 ppm. In comparison, the signals of the methyl groups in the prenyl moieties of the enzymatic products of CdpNPT are significantly up-field shifted to 0.9 to 1.1 ppm.…”
mentioning
confidence: 97%
“…Signals for the four protons at positions 4, 5, 6 and 7 of the indole ring were clearly observed (Table S1), and revealed that the prenyl moiety is connected to N-1 or C-2 of the indole ring. The signals of the methyl groups in the reverse prenyl moieties attached to C-2 of the indole rings of some diketopiperazine derivatives, for example, in echnulin-and isoechinulin-type alkaloids, [2][3][4] in deoxybrevianamide E [5] or okaramines, [6,7] were usually found in the range of 1.40 to 1.55 ppm. In comparison, the signals of the methyl groups in the prenyl moieties of the enzymatic products of CdpNPT are significantly up-field shifted to 0.9 to 1.1 ppm.…”
mentioning
confidence: 97%
“…The convergent total synthesis of (+)-okaramine J (10) was achieved by Roe et al in 2003. 10) The first enantioselective total synthesis of a member of the okaramine family, okaramine N (14), was accomplished by Baran et al in 2003. 11) In 2004, the total synthesis of okaramine C (3) was completed by Hewitt et al 12) All stereoisomers of okaramine M were synthesized by Iizuka et al and the reported structure of okaramine M (13a) was revised to 13b. …”
Section: )mentioning
confidence: 99%
“…Isoprenyl group was afforded after partial reduction of the alkyne introduced by N 8 -alkylation using 2-bromo-2-methylbut-3-yne. [129] Alkylative cyclization Cyclization with electrophiles (A, Scheme 5): This procedure uses the reactivity of indole nucleous of tryptamine or tryptophan with alkylating agents over the substituted 3-position, followed by in situ capture of the resulting indoline by the protected lateral amine.…”
mentioning
confidence: 99%
“…Total synthesis of (+)-okaramine C (11). [129] [133] (AE )-debromoflustramides B and E and (AE )-debromoflustramines B and E have been prepared using this procedure. [134] Nakagawa et al synthesized (AE )-esermethole (112) using an alkylative cyclization.…”
mentioning
confidence: 99%